Implementation of PDCA-Based Curriculum Management in Improving the Quality of Islamic Education - Tri Sephiani Yusuf; Taufani Chusnul Kurniatun; Cepi Triatna (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2026)
Abstract This study aims to examine the contribution of curriculum management implementation to improving the quality of education through the integration of the national curriculum and the school's specific curriculum. The focus of the analysis is on the application of the Plan, Do, Check, and Act. So that the learning process is structured, controlled, and continuous. The research uses a qualitative descriptive approach with data collection techniques in the form of in-depth interviews, observations, and documentation studies. Interviews were conducted with six informants, including school principals, deputy heads of curriculum, subject teachers, and homeroom teachers. Informants were selected using snowball sampling, starting with key informants and expanding based on recommendations until the information obtained was deemed sufficient. The interviews were conducted based on the 3M principle, namely active listening, understanding the meaning in context, and systematic note-taking. The findings show that the Plan stage covers curriculum formulation and development, Do focuses on curriculum implementation in learning, Check emphasizes monitoring and evaluation of implementation, while Act involves continuous improvement follow-up. The application of this cycle makes planning more focused, implementation more controlled, evaluation more systematic, and improvement responses more adaptive to learning needs. The integration of the national curriculum and the specific curriculum results in learning that not only meets academic standards but is also relevant to the characteristics of the students. Theoretically, this study enriches the understanding of PDCA as a managerial framework in curriculum development and continuous improvement of education quality. Although a number of studies have reviewed PDCA in the context of education quality management, studies that specifically integrate PDCA-based curriculum management with the internalization of Islamic values in secondary education are still relatively limited. Therefore, this study offers an integrative model of PDCA-based curriculum management that simultaneously strengthens academic quality and Islamic character building. Keywords: Curriculum Implementation, Curriculum Integration, Quality Improvement